Performative shamelessness on young women's social network sites: Shielding the self and resisting gender melancholia - Dobson, Amy (2014)
In this paper, I ask what the self-representations of young women on social network sites can tell us about the conditions and experience of inhabiting femininity in the digitally mediated post-feminist context. First, I outline four conditions of post-feminist girlhood that I suggest young women must navigate in the processes of subjectivity construction. I then describe some of the common kinds of performativity found on a small selection of social network site profiles owned by young Australian women. I suggest that a 'shameless' affect may be a necessary form of self-protection for these young women, operating in contexts that appear to require copious amounts, and intense forms, of self-display. The kind of 'shameless' affectations we can see on young women's social network site profiles may also be a way of resisting the dominant terms by which contemporary femininity is understood as normatively 'melancholic' or damaged.